2013
DOI: 10.14202/vetworld.2013.739-743
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antibiogram of Staphylococcus, Streptococcus and Escherichia coli isolates from clinical and subclinical cases of bovine mastitis

Abstract: Aim: The present study was aimed to isolate and evaluate the continuous change in the pattern of drug resistance showed by different mastitogenic organisms, isolated from clinical and subclinical cases of mastitis. Materials and Methods:The study was carried out using 150 milk samples received from various clinical and subclinical cases, from which the causative organisms were isolated and subjected to in vitro antibiotic sensitivity test. Results:The bacteriological analysis of the samples indicated the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
16
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 8 publications
9
16
5
1
Order By: Relevance
“…In this study, a total of 300 raw milk samples were studied and from these 300 raw milk samples, 75 (25%) milk samples were contaminated with E. coli. This is in agreement with the report by Mohanty et al, 15 who found (21%) from India. The current finding was relatively higher as compared to the studies by Lye et al, 16 & Addo et al, 17 who reported 8.75% and 11.2% from Malaysia and Ghana, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, a total of 300 raw milk samples were studied and from these 300 raw milk samples, 75 (25%) milk samples were contaminated with E. coli. This is in agreement with the report by Mohanty et al, 15 who found (21%) from India. The current finding was relatively higher as compared to the studies by Lye et al, 16 & Addo et al, 17 who reported 8.75% and 11.2% from Malaysia and Ghana, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, a total of 300 raw milk samples were studied and from these 300 raw milk samples, 75 (25%) milk samples were contaminated with E. coli. This is in agreement with the report by Mohanty et al, 15 who found (21%) from India. The current finding was relatively higher as compared to the studies by Lye et al, 16 and Addo et al, 17 who reported 8.75% and 11.2% from Malaysia and Ghana, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…Statistically significant difference (P< 0.05) among the sample types in the prevalence of S. aureus was recorded. A similar report was also made by previous researchers (Abebe et al, 2013;Reta et al, 2016) that S. aureus was 15.5 and 24.2% in raw milk samples respectively in Ethiopia and in the other parts of the world which is contrary to this; different literatures revealed a very significant isolation rate of S. aureus from raw milk samples (Olatunji et al, 2009;Pourhassan and Taravat-Najafabadi, 2011;Mohanty et al, 2013;Sanaa et al, 2005).…”
Section: Discussionsupporting
confidence: 70%